2020
DOI: 10.1097/wnn.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subtle Verbal Memory Deficits in Premanifest Huntington Disease Using the California Verbal Learning Test

Abstract: Background: Verbal memory impairment in individuals with Huntington disease (HD) is well-documented; however, the nature and extent of verbal memory impairment in individuals with premanifest HD (pre-HD) are less understood. Objective: To evaluate verbal memory function in individuals with pre-HD by comparing their performance on the California Verbal Learning Test to that of individuals with a clinical diagnosis of HD and that of a demographically simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…However, our results suggest that by allowing for the recall of any item from either learned list (A or B), the LASSI-L paradigm enhanced the combined effects of both proactive and retroactive interference on the final Delayed Recall section. This overall effect may have contributed to the larger effect size that was recorded on the Delayed Free Recall section in our study (d = 1.652, P ≤ 0.001) compared with the effect that was reported for Long Delay Free Recall on the CVLT-II in a similar preHD population (d = 0.40, P = 0.05) (Holden et al, 2020). Performance on the Interference sections (PSI and RSI) of the LASSI-L was not significantly correlated with performance on the Stroop Word Reading subtest (the only other neuropsychological test that survived multiple comparisons in our battery) (r = 0.257, P = 0.397).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, our results suggest that by allowing for the recall of any item from either learned list (A or B), the LASSI-L paradigm enhanced the combined effects of both proactive and retroactive interference on the final Delayed Recall section. This overall effect may have contributed to the larger effect size that was recorded on the Delayed Free Recall section in our study (d = 1.652, P ≤ 0.001) compared with the effect that was reported for Long Delay Free Recall on the CVLT-II in a similar preHD population (d = 0.40, P = 0.05) (Holden et al, 2020). Performance on the Interference sections (PSI and RSI) of the LASSI-L was not significantly correlated with performance on the Stroop Word Reading subtest (the only other neuropsychological test that survived multiple comparisons in our battery) (r = 0.257, P = 0.397).…”
Section: Discussioncontrasting
confidence: 54%
“…Each test has relative advantages: The CVLT allows measures of learning strategies (eg, semantic clustering and serial order); the LASSI–L has robust measures of interference. Regardless, our results provide further evidence that verbal learning tests are sensitive to early cognitive changes in individuals with preHD, and they should be incorporated with greater frequency in the assessment and monitoring of this specific population (Holden et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…By the time individuals are diagnosed with manifest HD, many will demonstrate measurable cognitive impairment on standardized neuropsychological assessments. [3][4][5][6][7][8] Therefore, it is crucial to examine the nature of neurocognitive changes that occur during the premanifest stages of HD, thereby improving the predictability of disease progression and possibly providing earlier opportunities for cognitive intervention. 9 Several studies have suggested that measures of executive function and processing speed-such as the Symbol Digits Modality Test (SDMT), Trail Making Test Part B, and Stroop-are particularly sensitive to early impairment in HD gene carriers.…”
mentioning
confidence: 99%
“…In view of the potentially prolonged nature of the premanifest stage, Ross and colleagues 2 proposed that premanifest HD be composed of the following 2 stages: presymptomatic HD (pre‐HD; furthest from HD diagnosis) and prodromal HD (pro‐HD; closest to HD diagnosis). By the time individuals are diagnosed with manifest HD, many will demonstrate measurable cognitive impairment on standardized neuropsychological assessments 3–8 . Therefore, it is crucial to examine the nature of neurocognitive changes that occur during the premanifest stages of HD, thereby improving the predictability of disease progression and possibly providing earlier opportunities for cognitive intervention 9 …”
mentioning
confidence: 99%